The Role Media in Consolidating and Promoting Environmental Citizenship in Society –Study Case Algerian Radio Channel 1- - djaffal, imene; belkhiri, radouane (Journal of Social Sciences and Humanities, 2021)
Environmental citizenship is the set of standards and values constituting the intrinsic motivation that makes the individual responsible towards their environment and drive them to adopt a positive and civilized behavior toward its elements and components. Media plays a leading role in inculcating these standards and values and in indoctrinating proper environmental behavior through the processes of environmental education, enculturation and sensitization. This has led to the emergence of a specialized environmental media in some countries which is led by specialized media professionals and it aims primarily at creating a public opinion that is aware of the danger of global environmental degradation and committed to environmental issues within the so-called responsible and effective citizenship. In Algeria, various media, including the Algerian radio, are making considerable efforts to raise awareness about environmental problems and to encourage citizens to join environmental protection efforts and reduce the damages caused by economic activities. This is because of its peculiarity as a mass communication outlet that enjoys a strong influence over a wide audience of different ages and groups. The radio program networks include various environmental media contents that aim at addressing various environmental issues and problems in Algeria, as well as highlighting the national strategy for environmental protection by addressing the variety of projected development programs and plans and tracking their impact on the ground. In addition to preparing and leading a series of environmental media campaigns launched at various local and global environmental events to raise awareness and sensitize citizens about the importance of adopting sound environmental ideas and values and adhering to rational environmental behaviors in order to enjoy a decent life in a clean and healthy environment. Our study therefore focuses on the role played by the first Algerian radio station in disseminating and inculcating the values of environmental citizenship in society, and thus to develop environmental responsibility among citizens.